2023
DOI: 10.1039/d3fo02217j
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry consumption protects against e-cigarette-induced vascular oxidative stress in mice

Maureen L. Meister,
Rafaela G. Feresin

Abstract: E-cigarettes provoke vascular oxidative stress through upregulation of pro-oxidant enzymes. Reactive oxygen species (ROS) produced by these enzymes, reduce nitric oxide (NO) bioavailability. Blackberry mitigates ROS and increases NO production, improving NO bioavailability and vascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…evaluated changes in the protein expression of pro-oxidant and inflammatory markers as an indicator of microvasculature in rats exposed to e-cigarettes. They concluded that blackberry consumption attenuated vascular oxidative stress caused by e-cigarette exposure [86]. Woolf et al (2023) found improvements in endothelial function in postmenopausal women with hypertension after 12 weeks of blueberry consumption; they attributed this effect to a reduction in oxidative stress and linked it to polyphenol metabolites found in plasma [87].…”
Section: The Role Of Cherry and Berry Consumption In Cardiovascular D...mentioning
confidence: 99%
“…evaluated changes in the protein expression of pro-oxidant and inflammatory markers as an indicator of microvasculature in rats exposed to e-cigarettes. They concluded that blackberry consumption attenuated vascular oxidative stress caused by e-cigarette exposure [86]. Woolf et al (2023) found improvements in endothelial function in postmenopausal women with hypertension after 12 weeks of blueberry consumption; they attributed this effect to a reduction in oxidative stress and linked it to polyphenol metabolites found in plasma [87].…”
Section: The Role Of Cherry and Berry Consumption In Cardiovascular D...mentioning
confidence: 99%
“…Meister et al (2023) evaluated changes in the protein expression of pro-oxidant and inflammatory markers as an indicator of the microvasculature in rats exposed to e-cigarette. They concluded that blackberry consumption attenuated vascular oxidative stress caused by e-cigarette exposure [86]. Woolf et al (2023) found improvements in endothelial function in postmenopausal women with hypertension after 12 week of blueberry consumption; they attributed this effect to a reduction in oxidative stress and linked it to polyphenol metabolites found in plasma [87].…”
Section: The Role Of Cherry and Berries Consumption In Cardiovascular...mentioning
confidence: 99%